Assessing Potential Factors Influencing the Efficacy of Immune Checkpoint Inhibitors with Radiation in Advanced Non-Small-Cell Lung Cancer Patients: A Systematic Review and Meta-Analysis. (13th January 2023) - Xu, Huilin; Cao, Dedong; Zhou, Dingjie; He, Anbing; Ge, Wei; Xu, Ximing
Abstract : Objective . Recent evidence suggests that combining radiotherapy (RT) with immune checkpoint inhibitors (ICIs) may result in better outcomes. In this study, we assessed the efficacy and safety of ICI plus radiation versus ICI alone and explored potential factors affecting its efficacy in advanced non-small-cell lung cancer (NSCLC) patients. Methods . The databases including PubMed and Embase were searched to retrieve eligible studies comparing the efficacy and safety outcomes in advanced NSCLC patients after ICIs ± RT treatments. We performed subgroup analyses to identify potential prognostic factors from radiation details and study types. The odds ratio (OR) of objective response rate (ORR) and disease control rate (DCR), hazard ratio (HR) of progression-free survival (PFS) and overall survival (OS), and risk ratio (RR) of adverse events were used to represent the outcome effects. Results . 26 eligible studies with 14192 cases were included. The results showed that the ORR (OR = 0.63, 95% CI: 0.42, 0.93; p  = 0.02) and DCR (OR = 0.55, 95% CI: 0.36, 0.82; p  < 0.01) of RT + ICIs groups were significantly higher than those of the ICIs alone group. The median PFS and OS for ICIs versus RT + ICIs were 2.2 versus 4.4 months and 9.0 versus 13.4 months, respectively. Patients in the ICIs plus RT group had a significantly better PFS (HR = 0.72, 95% CI: 0.64, 0.81; p  < 0.01) and OS (HR = 0.74, 95% CI: 0.65, 0.83; p  < 0.01) when compared to those in the ICIs group. In terms of adverse events, the risk of pneumonia was not significantly increased in patients treated with both ICIs and RT when compared to ICIs group alone (risk ratio = 0.89; 95% CI: 0.55, 1.44; p  = 0.63). The correlation analysis found that PFS was significantly correlated with OS (p = 0.02). The subgroup analysis results showed that significant improvements in OS were observed in non-palliative RT group (HR = 0.29, 95% CI: 0.13, 0.65; p  < 0.01) and extracranial RT group (HR = 0.70, 95% CI: 0.59, 0.83; p  < 0.01). RT type could also be a prognostic factor associated with the OS (for conventional RT: HR = 0.68 and p  = 0.22; for stereotactic body radiation therapy: HR = 0.77 and p  < 0.01). However, concerning RT timing, the results showed a similar trend in reducing mortality risk (for previous RT: HR = 0.64 and p  = 0.21; for concurrent RT: HR = 0.35 and p  = 0.16). Conclusion . RT plus ICIs is associated with improved survival for advanced NSCLC patients, especially for those with non-palliative RT. Further clinical trials are needed to validate its effect on survival outcomes.